2013
DOI: 10.1590/s1415-47572013005000004
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of Toll-like receptor 5 among pig populations

Abstract: The Toll-like receptor 5 (TLR5) recognizes flagellin of Gram-positive and -negative bacteria and plays an important role in the host defense system. Here, we surveyed single nucleotide polymorphisms (SNPs) in the coding sequence of the porcine TLR5 gene in 83 individuals from five pig breeds, these including Chinese local populations and Western commercial pig breeds. A total of 19 medium polymorphic SNPs (0.25 < PIC < 0.5) were identified, three of which were missense mutations that clustered within the extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Some non-synonymous polymorphisms within the coding sequence of human TLR5 affect its signaling capacity and human disease susceptibility 52 , 53 . Sequence polymorphisms in tlr5 and associated changes in functionality have been identified within various animal species 54 57 . Several non-synonymous polymorphisms in both the ECD or the ICD were described to attenuate TLR5 responses towards flagellin, demonstrated for both porcine (polymorphisms R148L and P402L) 56 and canine TLR5 (polymorphisms C100T and T1844C) 55 .…”
Section: Discussionmentioning
confidence: 99%
“…Some non-synonymous polymorphisms within the coding sequence of human TLR5 affect its signaling capacity and human disease susceptibility 52 , 53 . Sequence polymorphisms in tlr5 and associated changes in functionality have been identified within various animal species 54 57 . Several non-synonymous polymorphisms in both the ECD or the ICD were described to attenuate TLR5 responses towards flagellin, demonstrated for both porcine (polymorphisms R148L and P402L) 56 and canine TLR5 (polymorphisms C100T and T1844C) 55 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, three missense mutations were identified in the extracellular domain with one of them shown to be important for flagellin recognition. SNPs have implications in various human diseases and although this relation has not be described for swine so far, analysis of polymorphism may provide a useful tool in the selection of disease-resistant animals in future (Yang et al, 2013).…”
Section: Toll-like Receptorsmentioning
confidence: 99%
“…Dominguez et al [20] identified one indel variant in the predicted TLR5 promoter sequence, which contributed to an additional STAT binding site and an increase in promoter activity. Compared with Western breeds, Chinese domestic pig breeds have higher genetic diversity and more haplotypes [21]. In this study, TLR5 and the Toll-like signaling pathway were determined by transcriptome analysis of E. coli F18-resistant and -sensitive weaned Sutai piglets (Meishan × Duroc).…”
Section: Introductionmentioning
confidence: 99%